2016
DOI: 10.1007/s12247-016-9253-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Study of Drug Release Properties of Curcumin from Polycaprolactone /Organomodified Montmorillonite Nanocomposite

Abstract: Purpose This study aims to intercalate polycaprolactone (PCL)/curcumin nanocomposite in the interlayer spaces of montmorillonite clay (MMT) modified with n-cetyl-N,N,Ntrimethylammonium bromide (CTAB) for improved drug release. Methods Curcumin-loaded polycaprolactone/organoclay nanoparticles prepared by nanoprecipitation method were characterized by determining the size, zeta potentials, and encapsulation efficiency. Scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Since the encapsulated drug carvedilol is lipophilic, the phospholipid molecules could easily entrap the drug. The hydrophobic nature of carvedilol also ensure very low drug loss into the surrounding aqueous phase during the formulation of ethosomes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the encapsulated drug carvedilol is lipophilic, the phospholipid molecules could easily entrap the drug. The hydrophobic nature of carvedilol also ensure very low drug loss into the surrounding aqueous phase during the formulation of ethosomes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning a report by Jain and (Jain and Datta, 2016). On the other hand, Bakre et al (2016) have documented 60-75% curcumin release from curcuminloaded polycaprolactone/organoclay nanoparticles after 6 hours in the phosphate buffer. The clay platelets are recognized as an impervious barrier to the diffused molecules, which forces them to follow a circuitous channel and caused a slower release scattering (Choudalakis and Gotsis, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The sustained release of drugs in MMT depends on its content, the increase of interlayer spacing, and its dispersion in the matrix [160]. The research results of Bakre et al [173] showed that in polycaprolactone/montmorillonite composite materials, as the concentration of MMT increases, the sustained release rate of curcumin slows down. The increased interlayer spacing after modification of MMT can optimize the sustained release performance.…”
Section: Drug Loading-release Of Mmtmentioning
confidence: 99%